Hemoptysis during general anesthesia in a diabetic patient with healed tuberculosis: a case report - Chung, Mee Young (Korean J Anesthesiol, 2017)
Hemoptysis is a common complication of pulmonary tuberculosis. Most of the cases of hemoptysis originate from hypertrophied bronchial arteries. Also, diabetes induces pulmonary vascular abnormalities such as endothelial dysfunction, inflammatory infiltration and pulmonary vascular remodeling. A 27-year-old male, with diabetes and a history of tuberculosis, underwent the procedure of pars plana vitrectomy under general anesthesia. After an uneventful intra-operative period, he had hemoptysis prior to extubation. Emergency fiberoptic bronchscopy showed blood plugs and spotted fresh blood at the right upper lobar bronchus. After successful embolization of the bronchial artery, the patient made a recovery and was discharged without experiencing any complication. Predisposing factors of hemoptysis in this case are presumed to be tuberculosis and diabetes. The bleeding might had been caused by the rupture of a weakened artery within the cavity in the right upper lobe, through expansion of the lung during manual ventilation by positive pressure.